Respuesta :

Answer:

G

Step-by-step explanation:

Using the rule of radicals

[tex]\sqrt{a}[/tex] × [tex]\sqrt{b}[/tex] ⇔ [tex]\sqrt{ab}[/tex]

Simplifying the radicals in the expression

[tex]\sqrt{52}[/tex]

= [tex]\sqrt{4(13)}[/tex]

= [tex]\sqrt{4}[/tex] × [tex]\sqrt{13}[/tex]

= 2[tex]\sqrt{13}[/tex]

------------------

[tex]\sqrt{117}[/tex]

= [tex]\sqrt{9(13)}[/tex]

= [tex]\sqrt{9}[/tex] × [tex]\sqrt{13}[/tex]

= 3[tex]\sqrt{13}[/tex]

Then

[tex]\sqrt{52}[/tex] + [tex]\sqrt{117}[/tex]

= 2[tex]\sqrt{13}[/tex] + 3[tex]\sqrt{13}[/tex]

= 5[tex]\sqrt{13}[/tex] → G

Crowds

Problem:-

[tex]{\small\sf{The\:expression \sqrt{52} + \sqrt{117} \:is \: equivalent \: to}}[/tex]

[tex]\small\bf{F.} \: \sf{13} [/tex]

[tex]\small\bf{G.}\sf \:5 \sqrt{13} [/tex]

[tex]\small\bf{H.}\sf\:6 \sqrt{13} [/tex]

[tex]\small\bf{J.}\sf\:13 \sqrt{13} [/tex]

Solution:-

[tex]\small\sqrt{52}+\sqrt{117}\sqrt{4•13} +\sqrt{9•13}\tiny\sf\purple{(Product\:Property)}[/tex]

[tex]\small{ \: \:\: \: \: \: \: \:=\sqrt{2²•13}+\sqrt{3²•13}\tiny\sf\purple{(Prime\:Factorization)}}[/tex]

[tex]\small{\: \:\: \: \: \: \: \:=\sqrt{2²}\sqrt{13}+\sqrt{3²}\sqrt{13}\tiny\sf\purple{(Product\:Property)}}[/tex]

[tex]\small{\: \:\: \: \: \: \: \:=2\sqrt{13}+3\sqrt{13}\tiny\sf\purple{(Simplify)}}[/tex]

[tex]\small{\: \:\: \: \: \: \: \:=5\sqrt{13}\tiny\sf\purple{(Simplify)}}[/tex]

Answer:-

So, the correct option is D.

=======================

#Hope it helps!

(ノ^_^)ノ